Effect of Acid‐Basic Sites Ratio on the Catalytic Activity to Obtain 5‐HMF from Glucose Using Al2O3‐TiO2‐W Catalysts. Issue 45 (4th December 2018) - Córdova‐Pérez, Gerardo E.; Torres‐Torres, Gilberto; Ortíz‐Chi, Filiberto; Godavarthi, Srinivas; Silahua‐Pavón, Adib A.; Izquierdo‐Colorado, Armando; Da Costa, Patrick; Hernández‐Como, Norberto; Aleman, Miguel; Espinosa‐González, Claudia G.
Abstract: A series of Al2 O3 ‐TiO2 ‐W materials with variation in W composition was prepared using an innocuous and easy sol‐gel method, under both acid and basic pH conditions. The morphology and composition of W in the materials were studied by Scanning Electron Microscopy (SEM) and Energy Dispersive X‐ray spectroscopy (EDS), respectively, Density of basic and acid sites by CO2 and NH3 temperature programmed desorption (TPD) technique, and physicochemical properties by N2 physisorption studies, X‐ray diffraction (XRD), and UV‐Vis spectroscopy. The catalytic properties of Al2 O3 ‐TiO2 ‐W were examined for the conversion of glucose to produce 5‐hydroxymethylfurfural (5‐HMF) and the best yield of 5‐HMFobtained with the catalyst of 5 w% W load. This high yield level was achieved when the catalyst with 2.35 acid‐basic sites molar ratio was probed. Abstract : 5‐HMF from glucose using Al2O3‐TiO2‐W: The acid‐basic sites molar ratio (NH3 /CO2 ) on surface of Al2 O3 ‐TiO2 ‐W catalysts and the catalytic yields, indicate that the 5‐HMF production is directed by mean of two routes A): when interactions between D‐Glucose and basic sites on material surface, allowed isomerization to D‐Fructose and B): when dehydration of D‐Fructose occurred by interacting with acid sites to form 5‐HMF.